Development of community-based tourism: Study in Kertayasa Village, Pangandaran Districts, West Java - Rifki Rahmanda Putra; Ute Lies Siti Khadijah; Cecep Ucu Rakhman; Evi Novianti (Masyarakat, Kebudayaan dan Politik, 2021)
Kertayasa Tourism Village is one of the leading tourism villages in the Pangandaran Districts, West Java Province. It is proven by having won various awards, one of which is the champion of the advanced tourism village category in the 2019 Nusantara Tourism Village Competition. The community’s role in developing the village’s potential with sustainable tourism is one of the keys to the tourism village’s success. This study aims to identify a general description of Kertayasa Village development as a tourism village, analyze the development concept of community-based tourism, and analyze the relationship between the development concept with the Sustainable Development Goals (SDGs). The research method used is a qualitative approach with case study design and interactive model analysis techniques. The key informants in this study were selected using purposive sampling techniques, including the elements of the Kertayasa Village apparatus, community leaders, and tourism practitioners. The results showed the criteria for developing Kertayasa Tourism Village based on attractions, amenities, accessibility, and ancillary services. The development pattern is a tourist attractions cluster model (Green Canyon), which stimulates the surrounding villages’ development. The development’s characteristic is bottom-up with community empowerment’s central issue in environment, economy, and social-cultural to supports SDGs.